Anelli ricorsivi fra saperi e territori. Dalla frammentazione alla complessità - Ceruti, Mauro; Lazzarini, Anna (Studi sulla Formazione/Open Journal of Education, 2019)
The text aims at illustrating the relationship between the production of space and the production of culture, and reflects on its epistemological and pedagogical implications from the modern to the global age. From the separation of knowledge and disciplines, conceived as territories divided by clear borders, to mobility and network that draw new knowledge maps: the transition from fragmentation to complexity takes shape.